Integrated LTCC Pressure/Flow/Temperature Multisensor for Compressed Air Diagnostics† - Nicolas Craquelin; Aurélie Barras; Peter Ryser; Grégoire Boutinard-Rouelle; Yannick Fournier; Thomas Maeder (Sensors, 2010)
We present a multisensor designed for industrial compressed air diagnostics and combining the measurement of pressure, flow, and temperature, integrated with the corresponding signal conditioning electronics in a single low-temperature co-fired ceramic (LTCC) package. The developed sensor may be soldered onto an integrated electro-fluidic platform by using standard surface mount device (SMD) technology, e.g., as a standard electronic component would be on a printed circuit board, obviating the need for both wires and tubes and thus paving the road towards low-cost integrated electro-fluidic systems. Several performance aspects of this device are presented and discussed, together with electronics design issues.